2011
DOI: 10.1098/rsif.2010.0575
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of fluid production in smooth adhesive pads of insects

Abstract: Insect adhesion is mediated by thin fluid films secreted into the contact zone. As the amount of fluid affects adhesive forces, a control of secretion appears probable. Here, we quantify for the first time the rate of fluid secretion in adhesive pads of cockroaches and stick insects. The volume of footprints deposited during consecutive press-downs decreased exponentially and approached a non-zero steady state, demonstrating the presence of a storage volume. We estimated its size and the influx rate into it fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 43 publications
1
65
0
Order By: Relevance
“…Hence, there is an optimal volume of pad secretion at which the pad adhesion reaches its maximum. Secretion accumulated during a few minutes floods the attachment pads ( figure 1c,d) [33]. In the flooded state, the capillary forces and pad adhesion are reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, there is an optimal volume of pad secretion at which the pad adhesion reaches its maximum. Secretion accumulated during a few minutes floods the attachment pads ( figure 1c,d) [33]. In the flooded state, the capillary forces and pad adhesion are reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In the flooded state, the capillary forces and pad adhesion are reduced. Yet after an insect takes several steps (seven steps for a cockroach on a smooth substrate), the pad secretion volume approaches a stationary state in which the accumulated secretion is largely transferred to the substrate and the fluid loss on the substrate is compensated with a rather slow influx of fluid [33]. High fluid loss on rough substrates (figure 1e,f ) causes adhesion reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the lipid-and carbohydrate-containing fluid may be rather costly in the wet-adhesion-based locomotion. Regarding the amount of organic matter inside the fluid, the cost of liquid production appears to be negligible (Dirks and Federle, 2010) but when the effects of, for example, fluid deficiency are taken into account, it might be rather costly for insects to utilize wet adhesion. To estimate costs of this kind of locomotion, quantitative data on the droplet volume left behind on the surface after the footstep are required.…”
Section: Introductionmentioning
confidence: 99%
“…In some flies, the fluid is released through pores under the terminal spatula (Gorb, 1998), whereas for other insect species lacking such pores, the liquid transportation is provided by a system of nanoscopically small porous channels (Schwarz and Gorb, 2003). For smooth adhesive pads in stick insects, it has been demonstrated that the amount of the fluid secreted into the contact zone changes with step frequency until a non-zero steady state is reached (Dirks and Federle, 2010). Based on experiments with beetles and flies, it has been concluded that both cohesive forces and surface tension of the pad secretion have a major contribution to the mechanism of adhesion in hairy systems (Stork, 1983;Langer et al, 2004;Gorb et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, if this layer is thin enough, both normal and tangential forces can be transmitted from the seta to the substrate just like for a dry contact (although with a different friction coefficient). No interference is observed in the wet region: stray light from the dorsal side of the seta tip and the high brightness of the background conceal the light interferences produced by two surfaces of similar refractive indices (glass substrate, n g % 1:52, and insect secretion, n w % 1:47 [29]). On the other hand, the liquid -air interface is present right before the first bright interference fringe.…”
Section: Resultsmentioning
confidence: 99%